Pendampingan Identifikasi Perkembangan Peserta Didik Di SMA Negeri 1 Wundulako - Saadillah, Andi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Teachers need to understand that identifying learner development is an integral part of the teacher's duties as an educator. By doing this assistance, teachers can prepare themselves professionally to face the challenges of teaching in the classroom. A professional teacher is one who can identify and respond to the needs and developmental levels of each learner. By mentoring the identification of learner development, teachers can develop this ability early on. Identifying learner development allows teachers to design learning that suits the needs and developmental levels of learners. The training method used involves a participatory approach with direct observation, interviews with principals, teachers and students, and filling out questionnaires in the form of guidelines in identifying the development of students based on their developmental aspects. Thus, this mentoring contributes to improving the quality of learning in the classroom. Learner development identification also enables teachers to help learners recognize and understand their abilities and potential. This can increase learners' motivation and self-confidence. By prioritizing learner development identification mentoring for teachers, we can ensure that teachers are ready to be effective, responsive educators who can positively impact the development of their learners.